Various Paradigms in Islamic Educational Thought: Fundamentalism, Modernism, and Liberalism - Eka Firmansyah; Tobroni; Muhamad (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Substantially, Islamic education contains meaning and purpose. According to Muljono Damopolii, the purpose of Islamic education has a significant contribution in giving birth to various types of education, such as military education, teacher education, Islamic education, and so on. Paradigms are oriented to basic meanings, perspectives on things, and the ability to create descriptions that drive change. This research was conducted with a library approach. Researchers collect articles related to various paradigms in Islamic education thinking. With that, it was found that the discussion about the Islamic education paradigm means linking it to the present context. Before discussing further the paradigm of Islamic education, the author should describe the meaning of the paradigm. The paradigm means (1) Cases used as samples or examples, (2) an Outline of basic concepts and postulations that become references in the research process, (3) Models in scientific theory, (4) Groups of thought systems, thinking frameworks, a link lists all the formations of a word showing the word's conjugation and declension. According to Mahmud, the paradigm is (1) a way of looking at something, (2) a model, pattern, or ideal. From these models, various phenomena are viewed and explained, (3) Total theoretical and methodological premises that define and describe a concrete scientific study.